Influence of hydrogen and various carbon monoxide concentrations on reduction behavior of iron oxide at low temperature - Abu Tahari, MN; Salleh, F; Saharuddin, TST; Dzakaria, N; Samsuri, A; Hisham, MWM; Yarmo, MA (Pergamon-Elsevier Science Ltd, 2024)
The aims of this study are to produce Fe3O4 from Fe2O3 using hydrogen (H-2) and carbon monoxide (CO) gases by focusing on the influence of these gases on reduction of Fe2O3 to Fe3O4 at low temperature (below 500 degrees C). Low reduction temperature behavior was investigated by using temperature programmed reduction (TPR) with the presence of 20% H-2/N-2, 10% CO/N-2, 20% CO/N-2 and 40% CO/N-2. The TPR results indicated that the first reduction peak of Fe2O3 at low temperature appeared faster in CO atmosphere compared to H-2. Furthermore, reducibility of first stage reduction could be improved when increasing CO concentration and reduction rate were followed the sequence as: 40% CO > 20% CO > 10% CO > 10% H-2. All reduction peaks were shifted to higher temperature when the CO concentration was reduced. Although, initial reduction by H-2 occurred slower (first peak appeared at higher temperature, 465 degrees C) compared to CO, however, it showed better reduction with Fe2O3 fully reduced to Fe at temperature below 800 degrees C. Meanwhile, complete reduction happened at temperature above 800 degrees C in 10% and 20% CO/N-2. Thermodynamic calculation revealed that CO acts as a better reducer than H-2 as the enthalpy change of reaction (Delta H-r) is more exothermic than H-2 and the change in Gibbs free energy (Delta G) at 500 degrees C is directed to more spontaneous reaction in converting Fe2O3 to Fe3O4. Therefore, formation of magnetite at low temperature was thermodynamically more favorable in CO compared to H-2 atmosphere. XRD analysis explained the formation of smaller crystallite size of magnetite by H-2 whereas reduction of CO concentration from 40, 20 to 10% enhanced the growth of highly crystalline magnetite (31.3, 35.5 and 39.9 nm respectively). All reductants were successfully transformed Fe2O3 -> Fe3O4 at the first reduction peak except for 10% CO/N-2 as there was a weak crystalline peak due to remaining unreduced Fe2O3. Overall, less energy consumption needed in reducing Fe2O3 to Fe(3)O(4 )by CO. This proved that CO was enhanced the formation of magnetite, encouraged formation of highly crystalline magnetite in more concentrated CO, considered better reducing agent than H-2 and these are valid at lower temperature. (C) 2018 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.